Implementasi Project Based Learning dalam Pembelajaran Abad 21 pada Mata Kuliah Kesehatan Perempuan dan Perencanaan Keluarga - Jusni Jusni; Arfiani Arfiani; Husnul Khatimah; Kurniati Akhfar; Tri Nur Fajri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education in Indonesia is experiencing development, students are required to compete in the era of industrial revolution 4.0 in the 21st century to be able to improve their abilities, namely collaboration, communication, creative and critical thinking and problem solving skills. So an effort is needed that can be applied to learning activities and one of them is through the application of the Project Based Learning learning model. This project-based learning is a learning strategy that empowers students to gain knowledge and understanding. The aim of this research is to increase student creativity through project-based learning to create teaching media to introduce the female reproductive organs and their functions. Classroom action research research design. The population of this research is all students taking women's health and family planning courses for the 2022-2023 academic year with a sample size of 13 odd semester (three) students. The data collection technique looks at activity during the lecture process and monitors the progress of projects carried out by students using observation assisted by instruments, namely written tests, performance tests and observation sheets. The results show an increase in learning outcomes in the category of students' thinking skills and creativity, which can be seen from the students' enthusiasm in completing the Teaching Aids for Introduction to Female Reproductive Organs project as well as presenting and publishing the results of their work. So it can be concluded that the application of the Project Based Learning (PjBL) learning model can improve the learning outcomes of thinking skills and creativity of students at the Tahirah Al Baeti Bulukumba Midwifery Academy for the 2022/2023 Academic Year.